Effect of dietary inclusion of mannan oligosaccharides on the efficacy of a novel hydrogen peroxide-inactivated vaccine against Streptococcus agalactiae in Nile tilapia - Ramos-Espinoza, Fernando Carlos [UNESP]; Cueva-Quiroz, Victor Alexander [UNESP]; Alvarez-Rubio, Norquis Caled [UNESP]; Paganoti de Mello, Nicoli [UNESP]; de Moraes, Julieta Rodini Engrácia [UNESP] (Wiley, 2024)
Mannan oligosaccharides (MOS) have shown to stimulate immune response in different fish species, but the results may appear contradictory and have not been tested in conjunction with vaccination. We hypothesized that dietary MOS supplementation could enhance efficacy and immune responses after immunization with a novel hydrogen peroxide-inactivated vaccine. Nile Tilapia, Oreochromis niloticus, fingerlings were distributed into four groups (supplemented or not, vaccinated or not) and were used to determine immune and hematological parameters and somatic indexes. For the bacterial challenge and vaccine efficacy test, fish were assigned to five experimental groups. Twenty-eight days after the feeding trial and vaccination, the groups were challenged intraperitoneally and monitored for 21 days. The relative percent survival of the groups basal diet-vaccinated and MOS diet-vaccinated were 98.1% and 100.0%, respectively. The dietary inclusion of MOS after vaccination for 28 days had no influence on vaccine efficacy, which could be explained because of the high efficacy of the vaccine itself. Therefore, we suggest that the contribution of MOS supplementation to immune responses after vaccination in fish would be greater for vaccines with lower efficacy, or when tested for heterologous challenges or for crossed protection.
Keywords: efficacy; immune response; immunostimulants; inactivated vaccines; vaccination